PHEROMONES and EXOCRINE GLANDS IN ISOPTERA - Costa-Leonardo, Ana Maria [UNESP]; Haifig, Ives [UNESP] (Elsevier Academic Press Inc., 2010)
Termites are eusocial insects that have a peculiar and intriguing system of communication using pheromones. The termite pheromones are composed of a blend of chemical substances and they coordinate different social interactions or activities, including foraging, building, mating, defense, and nestmate recognition. Some of these sociochemicals are volatile, spreading in the air, and others are contact pheromones, which are transmitted by trophallaxis and grooming. Among the termite semiochemicals, the most known are alarm, trail, sex pheromones, and hydrocarbons responsible for the recognition of nestmates. The sources of the pheromones are exocrine glands located all over the termite body. The principal exocrine structures considered pheromone-producing glands in Isoptera are the frontal, mandibular, salivary or labial, sternal, and tergal glands. The frontal gland is the source of alarm pheromone and defensive chemicals, but the mandibular secretions have been little studied and their function is not well established in Isoptera. The secretion of salivary glands involves numerous chemical compounds, some of them without pheromonal function. The worker saliva contains a phagostimulating pheromone and probably a building pheromone, while the salivary reservoir of some soldiers contains defensive chemicals. The sternal gland is the only source of trail-following pheromone, whereas sex pheromones are secreted by two glandular sources, the sternal and tergal glands. To date, the termite semiochemicals have indicated that few molecules are involved in their chemical communication, that is, the same compound may be secreted by different glands, different castes and species, and for different functions, depending on the concentration. In addition to the pheromonal parsimony, recent studies also indicate the occurrence of a synergic effect among the compounds involved in the chemical communication of Isoptera. (C) 2010 Elsevier B.V.